Purchasing Decisions and Hotel Customer Satisfaction Through Service Quality and Marketing Stimulus - Abdul Haris; Muhammad Bakri; M. Maulana; Muhammad Erfan; Muh. Asdar (International Journal of Artificial Intelligence Research, 2022)
The purpose of the study was to find out by analyzing the effect of service quality and marketing stimulus on the purchasing decisions of star hotel customers in West Sulawesi; service quality and marketing stimulus on the satisfaction of star hotel customers in West Sulawesi; The effect of purchasing decisions on customer satisfaction for star hotels in West Sulawesi; The influence of service quality and marketing stimulus on customer satisfaction through the decision to buy five-star hotels in. The research method used is a descriptive survey and an explanatory survey. The population of this study is the overall customers of five-star hotels in West Sulawesi, where the number of members is unknown. The number of samples in this study used the Lemeshow formula, so the full selection was 100. The results of this study indicate that service quality and marketing stimulus directly have a positive and positive effect. Significant to the decision to purchase five-star hotels in West Sulawesi; Service quality directly has a positive but not significant impact on customer satisfaction for star hotels in West Sulawesi; Marketing stimuli and purchasing decisions directly have a positive and significant effect on customer satisfaction for star hotels in West Sulawesi; Service quality and marketing stimulus indirectly have a positive and insignificant impact on customer satisfaction through purchasing decisions for star hotels in West Sulawesi.